Assessment of the Therapeutic Potential of Melatonin for the Treatment of Osteoporosis Through a Narrative Review of Its Signaling and Preclinical and Clinical Studies - Zhao, Yongchao; Shao, Guoxi; Liu, Xingang; Li, Zhengwei (Frontiers in Pharmacology, 2022)
Melatonin is a bioamine produced primarily in the pineal gland although peripheral sites including the gut may also be its minor source. Melatonin regulates various functions including circadian rhythm, reproduction, temperature regulation, immune system, cardiovascular system, energy metabolism, and bone metabolism. Studies on cultured bone cells, preclinical disease models of bone loss, and clinical trials suggest favorable modulation of bone metabolism by melatonin. This narrative review gives a comprehensive account of the current understanding of melatonin at the cell/molecular to the systems levels. Melatonin predominantly acts through its cognate receptors of which melatonin receptor 2 (MT2R) is expressed in mesenchymal stem cells (MSC), osteoblasts (bone-forming), and osteoclasts (bone-resorbing). Melatonin favors the osteoblastic fate of MSC, stimulates osteoblast survival and differentiation, and inhibits osteoclastogenic differentiation of hematopoietic stem cells. Produced from osteoblastic cells, osteoprotegerin (OPG) and receptor activator of nuclear factor kappaB ligand (RANKL) critically regulate osteoclastogenesis and melatonin by suppressing the osteoclastogenic RANKL and upregulating the anti-osteoclastogenic OPG exerts a strong anti-resorptive effect. Although the anti-inflammatory role of melatonin favors osteogenic function and antagonizes the osteoclastogenic function with the participation of SIRT signaling, various miRNAs also mediate the effects of the hormone on bone cells. In rodent models of osteoporosis, melatonin has been unequivocally shown to have an anti-osteoporotic effect. Several clinical trials indicate the bone mass conserving effect of melatonin in aging/postmenopausal osteoporosis. This review aims to determine the possibility of melatonin as a novel class of anti-osteoporosis therapy through the critical assessment of the available literature.